Asia Pacific: Heal History – Build Peace, Trust And Hope For The Future (Could Pancasila Be Applied Regionally?) - Lawler, Barbara (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2023)
This paper respectfully and humbly attempts to describe a perspective on peacebuilding in the Asia Pacific region. It will emphasize the significant connection between personal and global change, one that seems to be overlooked to our detriment in overly systems-focused approaches to creating peace. It was once, pertinently or impertinently, commented by UK journalist, Peter Howard, that the problems sitting around the table at international conferences, or even the UN, are always more pressing than the problems sitting on the table. It will draw from real-life stories of those who have experienced change of heart leading to personal, family, community and sometimes national and international change. There will be a focus on Indonesia and Australia, healing history with Japan, Muslim-Christian relations, colonial history, including some evidential experience from Papua New Guinea, the Solomon Islands and other Pacific Island countries. References to the experience of countries outside the Asia-Pacific region will be made where the principles support the position that some big changes, national and international, have come about significantly through moral and spiritual change in individuals. It will attempt to respond to the question of whether our region with its extensive diversity, can model for the world the Pancasila, the peace, trust, hope and healing for which it longs. Keywords: Healing, Peace, Trust, Hope, Pancasila.